Biologists in the age of totalitarianism : personal reminiscences of ornithologists and other naturalists - Nowak, Eugeniusz (Cambridge Scholars Publishing, 2018)
This fascinating volume resulted from one man's frustration with the series of whitewashed obituaries and laudations he had to endure in his long career in West Germany. These were often of biologists who had worked in the Third Reich, a period generally skipped over in such eulogies. Dr Eugeniusz Nowak, born in Poland in 1933, therefore decided to do some historical research of his own. His series of controversial 'alternative' biographies of mainly German biologists in various journals soon grew into a successful book, with German, Russian and Polish editions. Now at last translated into Eng.